Follicular Lymphoma In Situ Presenting as Dermatopathic Lymphadenopathy - Orah Nnamdi Obumneme; Igbokwe Uche; Banjo Adekunbiola; Akinde Ralph; Irurhe Nicholas (Case Reports in Pathology)
Introduction. Follicular lymphoma in situ (FLIS) is a recently described entity with few cases recognized worldwide. To our knowledge, this is the first FLIS reported from West Africa. Case Presentation. We present the case of a 48-year-old civil servant with axillary lymphadenopathy discovered on routine mammography. On histology, a predominant reactive change with aggregates of melanophages was seen prompting a diagnosis of reactive lymphadenopathy. Immunohistochemistry done in our laboratory showed CD10 and Bcl-6 positive germinal centres with a small population of Bcl-2 positive germinal centre centre cells that were limited to some of the germinal centres. Conclusion. This highlights the use of immunohistochemistry in lymph node pathology—a resource which is very limited in our environment.